Hypersensitivity to amphetamine's psychomotor and reinforcing effects in serotonin transporter knockout rats: Glutamate in the nucleus accumbens. (30th August 2020) - Caffino, Lucia; Verheij, Michel M. M.; Roversi, Karine; Targa, Giorgia; Mottarlini, Francesca; Popik, Piotr; Nikiforuk, Agnieska; Golebiowska, Joanna; Fumagalli, Fabio; Homberg, Judith R.
Abstract : Background and Purpose: Amphetamine (AMPH) use disorder is a serious health concern, but, surprisingly, little is known about the vulnerability to the moderate and compulsive use of this psychostimulant and its underlying mechanisms. Previous research showed that inherited serotonin transporter (SERT) down‐regulation increases the motor response to cocaine, as well as moderate (as measured during daily 1‐h self‐administration sessions) and compulsive (as measured during daily 6‐h self‐administration sessions) intake of this psychostimulant. Here, we sought to investigate whether these findings generalize to AMPH and the underlying mechanisms in the nucleus accumbens. Experimental Approach: In serotonin transporter knockout (SERT −/− ) and wild‐type control (SERT +/+ ) rats, we assessed the locomotor response to acute AMPH and i.v. AMPH self‐administration under short access (ShA: 1‐h daily sessions) and long access (LgA: 6‐h daily sessions) conditions. Twenty‐four hours after AMPH self‐administration, we analysed the expression of glutamate system components in the nucleus accumbens shell and core. Key Results: We found that SERT −/− animals displayed an increased AMPH‐induced locomotor response and increased AMPH self‐administration under LgA but not ShA conditions. Further, we observed changes in the vesicular and glial glutamate transporters, NMDA and AMPA receptor subunits, and their respective postsynaptic scaffolding proteins as function of SERT genotype and AMPH exposure (baseline, ShA, and LgA), specifically in the nucleus accumbens shell. Conclusion and Implications: We demonstrate that SERT gene deletion increases the psychomotor and reinforcing effects of AMPH and that the latter is potentially mediated, at least in part, by homeostatic changes in the glutamatergic synapse of the nucleus accumbens shell and/or core. Abstract :